The Mental Health Literacy and Stigma Scale—Bilingual Cultural Adaptation: Validity and Reliability Pilot Study in Nursing Students - Maria José Nogueira; Síria Sas; Lucía Rodríguez; Andrea Carbonero; Uxía Bello; Leandro Nascimento; Susana Mendonça; Delfina Teixeira (Nursing Open)
ABSTRACT Aim To describe and evaluate the psychometric properties (reliability and construct validity) of the Mental Health Literacy and Stigma Scale‐Bilingual (MHLaSS‐B). Design This is a methodological study designed in a convenience sample of 271 Portuguese and Spanish nursing students who volunteered to participate in the research. Methods The Mental Health Literacy and Stigma Scale‐Bilingual version (Spanish and Portuguese) was used for data collection. MHLaSS‐B intercultural adaptation followed three stages: translation, back‐translation and pilot test and the thinking‐aloud techniques. Content validity was performed by Content Validity Index and Modified Kappa statistic. Construct validity and reliability tests were performed. Internal consistency was assessed by Cronbach's alpha. Data were analysed using SPSS programs. Ethics committee approval and permission from the institution involved were obtained. Results The MHLaSS‐B has 28 items of one‐factor structure. Cronbach's alpha was 0.702. The cumulative variance explained was 23.14%. Respondents show High literacy and Low Stigma (M = 23.4). Patient or Public Contributions The availability of the MHLaSS‐B allows the general population of Portugal and Spain to have a versatile instrument for assessing stigma and MHL. The MHLaSS‐B presents good psychometric properties, and it can be a useful tool for novice health workers to better understand the aspects they should pay attention to manage MHL and stigma successfully. The MHLaSS‐B is a reliable, adaptable instrument that is now available and it can be used in investigation, teaching and clinical practice.